Pedagogical Approaches to Grammar Instruction in Libyan Secondary Schools: Teachers’ Prespectives (Comprehensive Journal of Science, 2026)
Teaching a foreign language needs appropriate methods and techniques that suit for both, syllabus and students’ level to make a great success. Therefore, this research aimed to investigate the   techniques and approaches used by the English teachers who were teaching grammar at first year secondary schools in Agelat. It attempted to shed light on some communicative techniques and activities that help students producing language because the syllabus is based on communicative approach.The tool of data collection is an interview. This study was conducted with English teachers of ten schools in Agelat. The interview was conducted with forty teachers they  were teaching first year classes.  The results of this study showed that the teachers still widely use the grammar translation method during the teaching process although the syllabus is based on the communicative approach. The findings, the researcher gave some recommendations that may help teachers to teach the English grammar effectively.